Mechanical running power and energy expenditure in uphill and downhill running - Gravina-Cognetti, F.; Chaverri, D.; Planas, A.; Montraveta, J.; Carrasco-Marginet, M.; Puigarnau, S.; Espasa-Labrador, J.; Iglesias, X. (Sports, 2025)
Trail running involves constant changes in terrain and slope, complicating the accurate assessment of energy expenditure during performance. This study aimed to examine the relationship between running power output (RPO), oxygen consumption (VO2), carbon dioxide production (VCO2), and energy expenditure per minute (EEmin) across positive and negative slopes in trained trail runners under standardized laboratory conditions. Fifteen male trail runners performed five randomized 5 min treadmill runs at 70% of VO2 maximal speed on -7%, -5%, 0%, +5%, and +7% slopes. VO2, VCO2, EEmin, respiratory exchange ratio (RQ), heart rate (HR), and RPO were recorded. Statistical analysis included Shapiro-Wilk tests for normality, repeated-measures ANOVA to compare variables across slopes, and Spearman or Pearson correlations between RPO and physiological variables. Moderate to strong positive correlations were found between RPO and VO2 (Rho = 0.80-0.84, p < 0.001) and between RPO and EEmin (Rho= 0.74-0.87, p < 0.01) across all conditions. These findings suggest that RPO measured via a wearable device may reflect changes in energy expenditure and supports the integration of wearable power metrics into training and nutritional strategies for trail running. However, further studies in female athletes, outdoor settings, extreme slopes, and altitude conditions are needed to confirm the generalizability of these results.